Notes on the Paleophilotes (Inderskia) panope (Eversmann, 1851) (Lepidoptera: Lycaenidae), a rare and little known lycaenid taxon for Europe - Morgun, Dmitry V. (Zootaxa, 2013)
Paleophilotes panope (Eversmann, 1851) is a poorly known species of Lycaenidae that was found in 1848 by A.M. Butlerov in the Inder Lake vicinities (West Kazakhstan). For one and a half centuries, until the beginning of 2000s this taxon had been known only by the two samples of the type series preserved in the Zoological Institute of Saint Petersburg (Russia) and thought to be extinct. The second mention on the species was in the second volume of “Butterflies of Russia and adjacent territories” (Tuzov et al. 2000), where photos of three new specimens were published. This material was collected by A.V. Dantchenko (Moscow, Russia) and his colleagues in the chalky Aktolagai plateau in the Western Kazakhstan, not far from the type locality. Unfortunately, these researchers did not provide any material to museums and therefore this taxon remained unknown for most specialists. In other publications only some pictures of this species were provided (Lukhtanov, Lukhtanov 1994; Tshikolovets 2003).